The Genre of the Middle Grade Graphic Problem Novel. Issue 1 (3rd July 2022) - Rudin, Shai
ABSTRACT: Since the beginning of the 21 st century, young adults' literature has seen a modus change, transitioning from realistic literature of the problem novel genre to graphic problem novels. This transition stemmed from changing reading habits and literacy levels, with younger generations seeking visuality in addition to texts. The aim of this article is to examine and map out the genre of the middle grade graphic problem novel from a structuralistic approach, which tends to include a distinct format, whereby the protagonist, who is facing a significant crisis, manages to overcome at least some issues. While this genre is similar to the realistic problem novel for young adults that was popular in the 1980s, it is unique in its protagonist characteristics, who I refer to as "hybrid heroes." These heroes encompass traits of both classical heroes and anti-heroes, deal with crises throughout most of the plot, and are in constant survival mode. Moreover, illustrations replace regular monologues, striving to convey what is going on within the protagonist's consciousness, yet with an added layer of humor. To map this genre, in this paper I analyze three middle grade graphic problem novels: Just Jaime by Terri Libenson, Heartstopper by Alice Oseman, and Middle School by James Patterson and Chris Tebbetts.